Case Series: Two Cases of an Atypical Presentation of Oral Granular Cell Tumour. (26th December 2012) - Cole, Emma; Rahman, Naomi; Webb, Roger
Abstract : This paper describes two cases of oral granular cell tumours with an atypical clinical presentation; both are in females aged between 45 and 63 years of age. Granular cell tumours are unusual soft tissue neoplasm of neural or Schwann cell origin. Oral GCTs usually present clinically as pink or yellow small sessile lesions. GCTs are usually benign in nature; however they can present in a malignant form in fewer than 2% of cases. In benign cases treatment is surgical and usually curative with extremely low recurrence rates.